2015
DOI: 10.1002/app.41831
|View full text |Cite
|
Sign up to set email alerts
|

Effect of moisture on cationic polymerization of silicone epoxy monomers

Abstract: Moisture in polymerization of a cationically cured silicone epoxy monomer blend is an important parameter that affects the resulting polymer properties. We report the kinetics of the cationic polymerization of epoxy monomers as a function of water concentration, directly quantified using Karl Fischer (KF) titration that was characterized using Fourier transform infrared (FTIR) spectroscopy and also the mechanical strength of resulting polymers via diametral tensile strength measurements. Methodology and result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Epoxides typically applied in cationic photopolymers include cycloaliphatic and aliphatic epoxy resin. The photoinitiated curing rate of cycloaliphatic epoxides is higher than that of aliphatic epoxides, but the cured resins usually have problems of internal stress and brittleness . Aliphatic epoxides have flexible structure units but the reactivity is low .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epoxides typically applied in cationic photopolymers include cycloaliphatic and aliphatic epoxy resin. The photoinitiated curing rate of cycloaliphatic epoxides is higher than that of aliphatic epoxides, but the cured resins usually have problems of internal stress and brittleness . Aliphatic epoxides have flexible structure units but the reactivity is low .…”
Section: Introductionmentioning
confidence: 99%
“…Crivello et al have reported that silicone–epoxy resins have higher photocuring rate than that of aliphatic epoxy, and even higher than common cycloaliphatic epoxy resins . Furthermore, the cured resins may have small stress and good toughness due to the introduction of organic silicone chain segment …”
Section: Introductionmentioning
confidence: 99%
“…Cationic photo‐polymerization is different from free‐radical in that it uses photo‐initiators to open one bond in the monomer rings rather than converting one carbon double bond to two single bonds. The main drawbacks with these reactions are inhibition by water vapor typically in industrial environments , shrinkage, and a slower reaction timeframe relative to acrylics. Inhibition by water occurs in a similar manner to acrylic's inhibition by oxygen but requires water vapor or high humidity to occur.…”
Section: Introductionmentioning
confidence: 99%
“…Ranaweera and colleagues reported the effect of moisture on polymerization of epoxy monomers. 20 Cai and Jessop 21 reported the effect of water on UV-initiated hybrid polymerization and the results showed decreased physical properties due to loss of crosslinking. To date, there is no report on the effect of water on methacrylate/epoxy-based dentin adhesives cured by visible light initiated hybrid polymerization.…”
Section: Introductionmentioning
confidence: 99%